New Approach for B-Mode Ultrasound (US) Evaluation of the Plantar Aponeurosis (PA) Thickness in Healthy Subjects - Abd Ellah, Mohamed Mahmoud Hamdy; Kremser, Christian; Strobl, Sylvia; Rauch, Stefan; Deml, Christian; Kronreif, Christian; Klauser, Andrea (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Purpose To compare ultrasound (US) measurements in the sagittal and axial plane of the plantar aponeurosis (PA) in healthy subjects.Materials and Methods PA thickness was measured in 40 healthy subjects (mean age: 34 years) by two radiologists using US in sagittal, axial medial and axial lateral planes. Subjects were classified according to gender (female and male) and age (18 – 35 versus 50 – 75 years). All measurements were compared and the interobserver agreement was calculated.Results The PA was medially significantly thicker than laterally (mean ± std 3.1 ± 0.7 mm versus 2.5 ± 0.5 mm respectively, P< 0.001). A significant difference was found between males and females (3.3 ± 0.7 mm versus 2.9 ± 0.6 mm medially and 2.7 ± 0.6 mm versus 2.3 ± 0.4 mm laterally, p < 0.05) and between the older and younger age groups (3.8 ± 0.6 mm versus 2.8 ± 0.4 mm medially and 3.1 ± 0.4 mm versus 2.3 ± 0.4 mm laterally, p < 0.001). Good interobserver agreement was detected (0.74).Conclusion Measurement of central and lateral fascicles of the plantar aponeurosis in both planes (sagittal and axial) is recommended in the daily routine.Key points Citation Format
Keywords: soft tissues; ultrasound; anatomy; foot